Pengukuran Kualitas Penggunaan Website Sistem Pakar Diagnosa Awal Mental Illness Psikosis Dengan Metode WebQual - Khairan AR; Rahmat Musfikar; Robbi Amanda Ilham; Bustami Yusuf (STEKOM PRESS, 2022)
A mental illness is a syndrome, psychological, or behavioral disorder in which a person is dysfunctional at work. The problem is that medical personnel or doctors who are professionals in the field of psychology are not comparable to mental illness, especially teenagers. The initial diagnosis by web based and using the Extreme Programming (XP) method. Meanwhile, the main objective of the research is to determine the quality of the web system based on the perceptions of respondents, namely Darul Ihsan Vocational High School students. Measuring the quality of an expert web system using the WebQual instrument. There are three aspects of WebQual that will be measured, namely: usability, information, and interaction quality. Based on the questionnaires distributed to respondents, the expert web system was developed to fulfill the three aspects of WebQual (usability, information, and interaction, with a score of 83.78%, 80%, and 82.97% in the good category.